A Survey of Key Generation Techniques in Wireless channels for Physical Layer Security - Joanne Gomes, Sujata Kadam (International Journal of Intelligent Systems and Applications in Engineering, 2024)
Nowadays wireless networks are highly concerned about security. Compared to wireless networks, wired networks are less prone to attacks. The physical layer eavesdropping attack has a significant impact on wireless network security. The use of cryptographic methods at the higher layers of the OSI model is necessary for traditional security in wireless networks. These cryptographic keys can be replaced with key generation at physical layer exploiting the unpredictable channel properties. Current methods for generating wireless keys at the physical layer are examined in this paper. Comprehensive surveys in this regard are conducted of the guiding principles, performance indicators, and key generation process. Techniques for enhancing the effectiveness of key generation are also reviewed. The difficulties of using the strategy in each situation are then discussed, along with key generation applications in diverse situations. The paper ends with several recommendations for future investigations.